Work, Employment and Unionization in Transition Houses: A Case Study of One Canadian Province - MacDonald, M. Maureen (University of Warwick, 1996)
Transition houses are small feminist organizations, providing emergency shelter to women and children who have been abused. They also are workplaces whose social organization divides women as managers and workers. This research, an institutional ethnographic case-study of nine transition houses in one Canadian province, examines how relations between the state and transition house have led to greater institutional power and control over transition house work, by women who are paid managers. This results in a reconstituted struggle for equality between women inside these settings. Mangerialism in the Canadian transition house movement has not been theorized.The argument advanced here is that conflict between workers and managers in transition houses is an inevitable outcome of the on-going struggle to develop feminist praxis within contradictory relations, shaped and influenced by transition house/state relations, dominant managerial discourses, and the exigencies of transition house work. In an attempt to resist and to limit managerial power and control over the labour process and over feminist praxis, transition house workers look for ways to develop their own collective power. Unionization as a vehicle for collective action is an obvious choice and it is one that transition house workers are pursuing.